A Highly Efficient Tumor‐Targeting Nanoprobe with a Novel Cell Membrane Permeability Mechanism. Issue 12 (24th January 2019) - Lei, Zhendong; Ding, Lin; Yao, Chenjie; Mo, Fengfeng; Li, Chenchen; Huang, Yanan; Yin, Xuelian; Li, Min; Liu, Jinliang; Zhang, Yong; Ling, Changquan; Wang, Yanli
Abstract: Efficient tumor targeting has been a great challenge in the clinic for a very long time. The traditional targeting methods based on enhanced permeability and retention (EPR) effects show only an ≈5% targeting rate. To solve this problem, a new graphene‐based tumor cell nuclear targeting fluorescent nanoprobe (GTTN), with a new tumor‐targeting mechanism, is developed. GTTN is a graphene‐like single‐crystalline structure amphiphilic fluorescent probe with a periphery that is functionalized by sulfonic and hydroxyl groups. This probe has the characteristic of specific tumor cell targeting, as it can directly cross the cell membrane and specifically target to the tumor cell nucleus by the changed permeability of the tumor cell membranes in the tumor tissue. This new targeting mechanism is named the cell membrane permeability targeting (CMPT) mechanism, which is very different from the EPR effect. These probes can recognize tumor tissue at a very early stage and track the invasion and metastasis of tumor cells at the single cell level. The tumor‐targeting rate is improved from less than 5% to more than 50%. This achievement in efficient and accurate tumor cell targeting will speed up the arrival of a new era of tumor diagnosis and treatment. Abstract : A graphene‐based tumor cell nuclear targeting fluorescent nanoprobe (GTTN) with cell membrane permeability targeting mechanism is developed. GTTN can recognize tumor cells in a very early stage and track them at the single‐cell level but does not enter into normal tissue cells. The tumor‐targeting rate is improved from less than 5% to more than 50%.